Efektivitas Sistem Kewaspadaan Dini dan Respon terhadap Pencegahan Kasus Gigitan Hewan Penular Rabies dengan Pendekatan Epidemiologi di Puskesmas BP Nauli Kota Pematangsiantar - Sodang Sidabutar; Lusiana Siagian; Yunardi Yunardi (Lembaga Pengembangan Kinerja Dosen, 2025)
Rabies is a deadly zoonotic disease and remains a public health threat in Indonesia, including in Pematangsiantar City. Although preventable through vaccination and rapid intervention, cases of animal bites transmitting rabies (HPR) continue to increase. The government has implemented an Early Alert and Response System (SKDR) for rapid detection and response, but its effectiveness at the community health center (Puskesmas) level needs to be evaluated. This study aims to analyze the effectiveness of SKDR implementation in preventing and controlling HPR bite cases at the BP Nauli Community Health Center in 2024 using a quantitative descriptive-analytical approach. Data were obtained through observation, interviews, and analysis of SKDR and PEP reports. The results showed that the majority of SKDR reports were complete (92.3%) and there were no reporting disruptions (92.3%). Fisher's exact test showed a significant relationship between SKDR implementation and disruptions in rabies reporting (p = 0.026). In conclusion, an optimal SKDR system improves the effectiveness of rabies reporting and response.